Estimation of serum uric acid level in association with pattern and severity of psoriatic arthritis - Ismael, Sakar Jamal; Mirza, Raouf Rahim; Ahmed, Ronak Saeed (Journal of Neonatal Surgery, 2025)
Background: Psoriatic arthritis (PsA), a chronic inflammatory disorder, is increasingly associated with hyperuricemia. This study aimed to estimate serum uric acid (SUA) levels in PsA patients compared to healthy controls and evaluate their association with disease activity and subtypes. Methods: A case-control study was employed, recruiting 40 PsA patients meeting Classification Criteria for Psoriatic Arthritis (CASPAR) criteria and 40 age- and gender-matched clinically healthy controls. Disease activity was assessed via the Disease Activity Index for Psoriatic Arthritis (DAPSA), and fasting SUA levels were measured enzymatically Results: The SUA levels did not show a statistically significant difference across the clinical patterns of PsA. The most common clinical pattern of PsA observed was Polyarthritis Rheumatoid like, found in 14 (35.0%) patients. The relationship between uric acid levels and the severity of arthritis was also examined. Among 3 (7.5%) patients in remission, the mean ± SD of uric acid was 4.60 ± 0.000, with a 95% CI of (4.60 - 4.60). For 29 (72.5%) patients with low disease activity, the mean ± SD was 4.81 ± 1.139, with a 95% CI of (4.3688 - 5.2353). In 8 (20%) patients with moderate disease activity, the mean ± SD of uric acid was 7.83 ± 1.84, with a 95% CI of (6.2951 - 9.3674). Therefore, the severity of the disease significantly affected SUA levels (P < 0.001). Conclusions: Research findings demonstrated that levels of SUA failed to show any connection to PsA clinical patterns. Higher disease activity of PsA led to increased SUA levels among PsA patients. Patients who were in remission stages demonstrated the lowest concentration of serum uric acid level, yet patients marked by moderate disease activity levels showed the highest serum uric acid levels..